2007
DOI: 10.1021/ie071136+
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Particle Size of Cobalt/Rhenium on Porous Alumina and the Effect on Fischer−Tropsch Catalytic Performance

Abstract: This paper addresses the effect of catalyst particle size distributions on Fischer−Tropsch catalytic performance for cobalt catalysts promoted by rhenium on alumina or modified alumina as catalyst support. The catalyst particle size will affect diffusion of reactants as well as of products. Some key findings are that the C5+ selectivity is rather constant for particle sizes up to ca. 400 μm and that the selectivity reduction thereafter is largely explained by an increase in the methane yield as the effective H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…The activity of the catalyst in FTS largely depends on the degree of reduction of the metal precursor. The shape and size of the metal particles, which control the number of active sites is also important [12]. A considerable amount of discussion has gone into establishing the existence of structure sensitivity or not in supported Co catalysts during the FTS.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the catalyst in FTS largely depends on the degree of reduction of the metal precursor. The shape and size of the metal particles, which control the number of active sites is also important [12]. A considerable amount of discussion has gone into establishing the existence of structure sensitivity or not in supported Co catalysts during the FTS.…”
Section: Resultsmentioning
confidence: 99%
“…The Barrett-Joyner-Halenda model assumes presence of only cylindrical pores and absence of pore networks. In reality, no simple pore geometry exists as demonstrated by Rytter et al [22]. Transmission electron microscopy images of the Co/c-Al 2 O 3 interphase showed that the alumina crystallites were entangled into each other in what appeared to be a chaotic fashion.…”
Section: X-ray Diffractionmentioning
confidence: 96%
“…Olefins can also be hydrogenated in a secondary reaction. There is evidence from experiments at low conversion and small catalyst particle size that the primary product is dominated by olefins, but for practical purposes the olefin to paraffin ratio is well above two for C3 and then diminishes rapidly with chain length [12].…”
Section: Catalyst Activitymentioning
confidence: 99%
“…It has been shown that above ca. 200 µm particle size the higher effective H2/CO ratio in the inner part of the pellets significantly reduces C5+ yield [12]. Therefore, an egg-shell catalyst design is preferred where only the outer parts are impregnated with active metal.…”
Section: Fischer-tropsch Reactorsmentioning
confidence: 99%
See 1 more Smart Citation